Network meta‐analysis of the outcome 'participant complete clearance' in nonimmunosuppressed participants of eight interventions for actinic keratosis: a follow‐up on a Cochrane review. (13th August 2013) - Gupta, A.K.; Paquet, M.
<x xml:space="preserve">Abstract</x> What's already known about this topic? Several interventions are effective for the treatment of actinic keratosis (AK). Due to the lack of direct comparisons between these interventions, their relative efficacy is unknown. What does this study add? Using network meta‐analysis, the relative efficacy of eight main interventions for AK was determined based on the outcome 'participant complete clearance'. With the exception of ingenol mebutate, the relative efficacy of the interventions was independent of the anatomical location of the lesions.